2003
DOI: 10.1074/jbc.m306684200
|View full text |Cite
|
Sign up to set email alerts
|

Precursors with Altered Affinity for Hsp70 in Their Transit Peptides Are Efficiently Imported into Chloroplasts

Abstract: Protein import into chloroplasts is postulated to occur with the involvement of molecular chaperones. We have determined that the transit peptide of ferredoxin-NADP(H) reductase precursor binds preferentially to an Hsp70 from chloroplast stroma. To investigate the role of Hsp70 molecular chaperones in chloroplast protein import, we analyzed the import into pea chloroplasts of preproteins with decreased Hsp70 binding affinity in their transit peptides. Our results indicate that the precursor with the lowest aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 60 publications
6
27
0
Order By: Relevance
“…These finding are therefore consistent with a role of the CNV chloroplast TP-like region in the CNV infection process. Chloroplast TPs have been postulated to interact with the chloroplast outer membrane as part of the initial stages of the import process (6,30). Consistent with the role of the CNV chloroplast TP-like region in chloroplast targeting is the presence of a predicted transmembrane binding region (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These finding are therefore consistent with a role of the CNV chloroplast TP-like region in the CNV infection process. Chloroplast TPs have been postulated to interact with the chloroplast outer membrane as part of the initial stages of the import process (6,30). Consistent with the role of the CNV chloroplast TP-like region in chloroplast targeting is the presence of a predicted transmembrane binding region (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…on May 9, 2018 by guest http://jvi.asm.org/ to the chloroplast stroma, where proteolytic removal of the TP occurs (2,22,30,37). Based on this and the other observations made thus far, we suggest that the CNV arm(ϩSVRI) sequence can function as a chloroplast TP that targets proteins to the stroma.…”
Section: Vol 80 2006 Cucumber Necrosis Virus Chloroplast Transit Pementioning
confidence: 82%
“…10E. Both FNRtp and its mutant (FNRtp-1234) having all of the H70BSs mutated were still able to support import (84). FNRtp was recently found to interact with Hsp93 only when it is located at the N-ter of preprotein (85).…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed that import defects of cphsc70 mutants are observed only in young true leaves. The presence of two systems may also explain why precursors with altered affinities for Hsp70 in their transit peptides are still efficiently imported into chloroplasts (Rial et al, 2003(Rial et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro binding assays have shown interactions between cpHsc70 and a recombinant transit peptide of the precursor to the small subunit of RuBP carboxylase (prRBCS; Ivey et al, 2000). However, precursors with altered affinities for Hsp70 in their transit peptides were still efficiently imported into pea (Pisum sativum) chloroplasts (Rial et al, 2003(Rial et al, , 2006. Using an antibody against the pea stromal cpHsc70, S78 (also named CSS1; Marshall and Keegstra, 1992;Nielsen et al, 1997), it was shown that no, or very little, importing precursors were precipitated by the anti-S78 antibody from the soluble fraction of solubilized total chloroplast membranes Nielsen et al, 1997), suggesting that cpHsc70 was not associated with importing precursors in vivo.…”
Section: Introductionmentioning
confidence: 99%